Effects of Chronic Intranasal Oxytocin on Behavior and Cerebral Glucose Uptake in Juvenile Titi Monkeys - Arias del Razo, Rocío (Psychoneuroendocrinology, 2019)
Intranasal oxytocin (IN OXT) has been proposed as a treatment for autism spectrum disorder (ASD); however, little is known about the effects of long-term exposure. This is the first study in a non-human primate species to examine how developmental exposure to chronic IN OXT affects juvenile’s interactions with family members, social preference for parents versus strangers, anxiety-like behavior, and cerebral glucose metabolism. Titi monkeys are socially monogamous and biparental; their family bonds share important characteristics with human family bonds. Fourteen males and 15 females were treated intranasally with saline (n=14) or 0.8 IU/kg OXT (n=15), daily from 12 to 18 months of age. Compared to SAL-treated animals, OXT-treated animals of both sexes spent significantly more time grooming other family members (F(1)=8.97, p=0.006). Overall, OXT-treated subjects were more social (F(1) = 8.35, p = 0.005) during preference tests. OXT-treated females displayed an enhanced preference for their parents (t=2.265, p=0.026). OXT-treated males had a blunted preference for their parents and an increase in the time spent near unfamiliar pairs (F1=10.89, p=0.001). During anxiety tests, OXT-treated males refused to complete the task more often than SAL-treated males and had longer latencies (p< 0.0001). Neuroimaging studies revealed that OXT-treated animals had higher glucose uptake across the social salience network as a whole after one month of treatment (F(1,9) = 1.07, p = 0.042). Our results suggest moderate prosocial effects of chronic IN OXT, that did not depend on anxiolytic properties. We also found important sex differences that should be considered in a translational context.